2011
DOI: 10.1177/0022034510390808
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Inflammation is Associated with Decreased Levels of the α1-, β1-, and α2-Subunits of sGC in Human Odontoblasts

Abstract: The nitric oxide (NO) receptor enzyme soluble guanylate cyclase (sGC) contains one prosthetic heme group as an αβ heterodimer, and two heterodimer isoforms (α(1)β(1), α(2)β(1)) were characterized to have enzyme activity. To test the irreversible inflammation-dependent regulation of sGC in odontoblasts, we incubated decalcified frozen sections of healthy and inflamed human third molars with antibodies against β-actin, nitrotyrosine, inducible nitric oxide synthase (iNOS), α(1)-, β(1)-, and α(2)-subunits of sGC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…Interestingly, IL-10, a cytokine that plays a central role in limiting host immune response to pathogens by promoting the development of Tregs is also upregulated (Farges et al, 2011 ). An increase in the production of NO, a free radical anti-inflammatory at high concentration (Connelly et al, 2001 ), is also observed in bacteria-challenged, inflamed dental pulps (Di Nardo Di Maio et al, 2004 ; Korkmaz et al, 2011 ). The role of NO in this context remains unclear but experiments have suggested that, besides its well-known roles in vascular tone and nociceptive input modulation, it may be implicated in dental pulp healing by promoting odontoblast-like cell differentiation and subsequent formation of reparative dentine (Mei et al, 2007 ; Yasuhara et al, 2007 ).…”
mentioning
confidence: 99%
“…Interestingly, IL-10, a cytokine that plays a central role in limiting host immune response to pathogens by promoting the development of Tregs is also upregulated (Farges et al, 2011 ). An increase in the production of NO, a free radical anti-inflammatory at high concentration (Connelly et al, 2001 ), is also observed in bacteria-challenged, inflamed dental pulps (Di Nardo Di Maio et al, 2004 ; Korkmaz et al, 2011 ). The role of NO in this context remains unclear but experiments have suggested that, besides its well-known roles in vascular tone and nociceptive input modulation, it may be implicated in dental pulp healing by promoting odontoblast-like cell differentiation and subsequent formation of reparative dentine (Mei et al, 2007 ; Yasuhara et al, 2007 ).…”
mentioning
confidence: 99%
“…Odontoblasts from healthy teeth were also found to be negative for NOS2 (Kawanishi et al, 2004 ; Kawashima et al, 2005 ; Mei et al, 2007 ). NOS2 synthesis was increased in inflamed pulps beneath caries lesions or when inflammation was experimentally induced with bacterial by-products (Kawanishi et al, 2004 ; Kawashima et al, 2005 ; Mei et al, 2007 ; Korkmaz et al, 2011 ), underscoring the importance of this enzyme in NO production in pulp inflammatory conditions. We observed NOS2 immunoreactivity in odontoblast and subodontoblast cells of the peripheral inflamed pulp, as previously reported in human teeth (Korkmaz et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly regulated at the transcriptional level and is involved in antibacterial defense by producing large amounts of NO, up to micromolar levels, for sustained periods of time (hours to days) (Nathan, 1992 ; Nussler and Billiar, 1993 ; MacMicking et al, 1997 ; Bogdan, 2001 ; Coleman, 2001 ; Guzik et al, 2003 ). Previous studies indicated that the NOS2 gene was not or weakly expressed in healthy dental pulps, but was sharply up-regulated in inflamed ones (Law et al, 1999 ; Di Nardo Di Maio et al, 2004 ; Kawashima et al, 2005 ; Korkmaz et al, 2011 ). Human odontoblasts showed a marked immunoreactivity for 3-nitrotyrosine (a biomarker for NO-derived peroxinitrite) in inflamed pulp, suggesting that these cells release NO upon NOS2 activation.…”
Section: Introductionmentioning
confidence: 96%
“…for 1 h. The reaction occurred with 0.05% 3.3-diaminobenzidine tetra-hydrochloride (Sigma-Aldrich) in 0.05 M Tris-HCl buffer, pH 7.6, containing 0.01% H 2 O 2 and 0.01% nickel ammonium sulfate, as described previously. 19 Incubations without the primary antisera served as controls.…”
Section: Immunohistochemistrymentioning
confidence: 99%